2009
DOI: 10.1115/1.3030945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesive Thickness and Properties on the Biaxial Interfacial Shear Stresses in Bonded Joints Using a Continuum Mixture Model

Abstract: In this work, an analytical model based on continuum mixture theories is developed to study the biaxial interfacial shear stresses in adhesive-bonded joints due to thermomechanical loading. The model predicts the effect of adhesive thickness and properties on the interfacial shear stresses. Two sets of governing partial differential equations are solved for the displacement field in each layer of the joint. The interfacial shear stresses between the adhesive and each adherend are determined using the constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Analytical work on adhesive bonding can be found in many literatures, for example [ 60 65 ]. Rose’s analytical solution [ 61 ] was used by Muller et al [ 66 ].…”
Section: Polymer/metal Bonded Composite Structuresmentioning
confidence: 99%
“…Analytical work on adhesive bonding can be found in many literatures, for example [ 60 65 ]. Rose’s analytical solution [ 61 ] was used by Muller et al [ 66 ].…”
Section: Polymer/metal Bonded Composite Structuresmentioning
confidence: 99%
“…However, this method cannot give a good prediction of the structured behavior if the material response is plastic. In addition, some of the research by Nayfeh and Nassar [12], and Nassar and Virupaksha [16] assumed perfect bonding, while others such as Alfano and Crisfield [22] treated the adhesive as a very thin layer, but none of the mentioned literatures modeled the failure of the bonding interface itself.…”
Section: Introductionmentioning
confidence: 97%
“…Closed form and classical series solutions were extensively used in Refs. [11][12][13][14][15][16], for making parametric studies of joint design. On the other hand, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate the extent of misalignment is related with the thermal stress generated at the interface during calcination. Analytical modelling study 24 has shown that interfacial shear stress due to thermomechnical loading increases with the increase of the adhesive/coating thickness, and thus larger shift/displacement is expected with thicker coatings (also see analysis in Figure S12 in Supplementary Materials).…”
mentioning
confidence: 99%